Typological parallels of motives of the author’s birthday and death day in the creative legacy of Lesya Ukrainka and Marina Tsvetaeva - Betko, Iryna (Poznańskie Studia Slawistyczne, 2024)
The article is devoted to a comparative analysis of motives of the author’s birthday and death day in the creative legacy of Lesya Ukrainka and Marina Tsvetaeva. The methodology is determined by the use of sources representing symbolic biographies of modernist writers. The paradigm of Lesya Ukrainka’s biography is set by the motif of unlucky birthday. The motif of a bitter fate in connection with the author’s birthday is heard in the final text of the cycle Poems about Moscow by Tsvetaeva. The placement of accents of life and death in this cycle allows us to consider it in the general typolog-ical series with Lesya Ukrainka’s poem Contra spem spero! The fourth text of Tsvetaeva’s cycle is marked by the pathos of protest against death. It echoes the poem by the Ukrainian writer, Do you remember, when I said… The research reveals a panorama of typological parallels in the context of the life and creativity of two outstanding writers.